Financial Administration Management at the Environment Department in Kotamobagu City - Dewi, Akhwani Mutiara; Sendouw, Recky; Wawointana, Thelma (Technium Social Sciences Journal, 2025)
This research aims to know, analyze, and describe the financial administration management of waste/cleaning service retribution at the Kotamobagu City Environment Department. This type of research is qualitative research. The results showed that financial administration management at the Kotamobagu City Environment Department consisted of planning, implementation, and reporting and accountability. The results of this study are Planning in financial administration management, especially waste/cleanup retribution at the Kotamobagu City Environment Department, has not been effective in terms of data collection for determining retribution rates and objects. Implementation which includes collection and deposit is less efficient because it still tends to be conventional (cash) and there is still a lack of public awareness to pay retribution. Reporting and accountability carried out by the treasurer of revenue is good. The suggestions given include that the Environment Department must manage the data collection of retribution objects to be more accurate, improve socialization and evaluation to the community regarding the waste/cleanliness retribution policy, the use of digital technology in the collection process can improve the efficiency and accuracy of retribution recording, improve waste transportation services and implement an open data system that allows the public to monitor the allocation of retribution funds.